(untitled) (Orinoquia, 2024)
Non-used waste obtained from edible mushroom production generates contamination due to a lack of environmental awareness, economic resources, and technical capacity to carry out their final disposal. This research evaluated the quality of organic compost obtained from the exhausted substrate of Orellana (Pleurotus pulmonarius) production in different treatments over three months. A red Californian earthworm (Eisenia foetida) was used to decompose the substrate, and the structure, composition, and porosity of the compost obtained were analyzed. The study used three treatments: 100% organic waste, 50% substrate - 50% organic, and 100% Orellana substrate, respectively, to evaluate variables (temperature and pH) as a function of time. The best treatment was determined by soil analysis tests, which showed T3 (100% Orellana residues) and better behavior regarding its final composition, providing a sustainable solution for waste management generated in this industry and encouraging more sustainable practices.